Implementation of farmer participatory research (FPR) in the transfer of cassava technologies in Indonesia - Utomo, Wani Hadi; Suyanto; Sinaga, Aldon (International Center for Tropical Agriculture, 2001)
A Farmer Participatory Research (FPR) approach has been used in two pilot sites located in Malang and Blitar districts of East Java. The objective of the work, which was executed since l994, was to enchance the development and adoption of efficient cassava production technologies that are able to maintain soil productivity, reduce erosion, and increase the income of cassava farmers. To achieve this objective, a Rapid Rural Appraisal method was employed. The involvement of farmers started from the identification of the problems and discussion of possible solutions. The results show that most farmers in the pilot site had been aware of soil degradation problems in their fields, as well as some technologies to overcome the problems. However, they hardly practiced the technologies on their field, because they thought that the technologies were too complicated and costly. After discussion with the project staff, they realized that some cassava production technologies are not as difficult and costly as they had earlier thought. They decided to establish demonstration plots to test their ideas. The technologies tested in the demonstration plots included erosion control practices, fertilizer application and the introduction of new cassava varieties. After the experiences obtained in the demonstration plots during the first year, collaborating farmers decided to test some promising technologies in their own fields during the following years. The number of collaborating farmers, as well as the farmers doing FPR trials in their own fields, increased in the third year. In addition, some farmers at the Wates site in Blitar district started to adopt the preferred technologies in their whole field. The numbers of farmers adopting soil conservation practices increased significantly in the following year (1998/99). In the Dampit site in Malang district, the adoption process started in 1999/2000. Farmers in Wates and Dampit are happy with the FPR approach. This approach increased the ability of farmers to try new technologies that they thought might increase their income, although the results were not yet sure. This approach also motivated farmers to actively obtain new knowledge by discussing their problems and ideas with extension personnel and others.